Public Transport Pricing in Nigeria - Wojuade, Christopher Adesola (Advances in Social Sciences Research Journal, 2017)
Public transport is an important social service to satisfy the travel needs of citizens. There is the need to regulate fare so that it can be affordable to the transit riders. This study examines pricing of public transport operation in Nigeria. The information on fare pricing and regulation was sourced from the management of public and private transport companies and executives of transport unions in Lagos. Also, 200 willing passengers were sampled using purposive incidental sampling technique to ascertain their views on the fare charged. There is no government agency regulating transit pricing in the country. Public transit operators perceived transport service as social function; hence they generate revenue that is not enough to cover costs. The private transit operators are profit conscious and as a result charge fare that realise enough revenue to cover all costs and make some profit. They also engage in nefarious activities such arbitrarily hiking of fare during traffic hold up, peak period, festive period, night and scarcity of fuel. The passengers’ perceived that transport fare is high and does not correspond to services being rendered especially by individually owned transit operators. The study concludes that transit pricing is not regulated in the country, which has socio-economic implications on the transit riders.